Perspectives on innovation governance: challenges and dilemmas - Mónica Edwards-Schachter; Hector Gonzalo Ordoñez-Matamoros (Novation, 2023)
Innovation governance has risen to prominence as a central theme in nurturing and framing contemporary debates surrounding innovation policies. This Special Issue features contributions that critically examine the “complexities of governance and the governance of complexity” (Jessop, 2020), aiming for a deeper understanding of innovation governance processes. The selected papers build on some discussions from the inaugural international NOvation Online Forum (held from 15 to 17 September 2021) around innovation policies and governance practices. The issue focuses on a critical approach to dilemmas and challenges associated with innovation governance in the context of sustainability transformations and its intricate relationships with ethical, social, economic, and environmental concerns.